Ocean surface wind vector retrievals using active and passive microwave sensing on ADEOS-II - Kasparis, Takis; Soisuvarn, Seubson; Jones, Wilma L. (My University, 2005)
Conventional "multiple-azimuth-look" space-borne scatterometers have been used to retrieve ocean surface wind vector for over three decades. However, the requirement for the antenna to view both forward and aft has made the scatterometer a difficult instrument to accommodate on remote sensing satellites with multiple earth-viewing sensors. In this paper, we present a new technique for ocean surface wind vector measurement using a "single-azimuth-look" combined active and passive microwave sensing from space. We demonstrate this methodology by using actual measurements of the ocean normalized radar cross section (sigma-0) and the radiometer-inferred wind magnitude respectively from the SeaWinds scatterometer and the Advanced Microwave Scanning Radiometer (AMSR) on-board the Advanced Earth Observing Satellite (ADEOS-II). For the scatterometer measurements, only the forward look, in the same direction as the AMSR measurements, is used. Owing to the biharmonic nature of the scatterometer anisotropic Geophysical Model Function (GMF), the retrieved wind direction consists of as many as four possible wind directions (aliases) at each wind vector cell (WVC). Alias selection is presented and performance is measured by comparison of the selected to the standard wind vector product from SeaWinds. Statistical analyses are performed and results show that it is feasible to measure ocean surface wind vector using single look geometry.
Keywords: Geoscience; Image converters; Microwaves; Oceanography; Meteorological satellites; Radiometers